A high-throughput pipeline for validation of antibodies - Sikorski, Krzysztof; Mehta, Adi; Inngjerdingen, Marit; Thakor, Flourina; Kling, Simon; Kalina, Tomas; Nyman, Tuula A; Stensland, Maria Ekman; Zhou, Wei; de Souza, Gustavo A; Holden, Lars; Stuchly, Jan; et al. (Nature methods, 2018)
Western blotting (WB) is widely used to test antibody specificity, but the assay has low throughput and precision. Here we used preparative gel electrophoresis to develop a capture format for WB. Fractions with soluble, size-separated proteins facilitated parallel readout with antibody arrays, shotgun mass spectrometry (MS) and immunoprecipitation followed by MS (IP-MS). This pipeline provided the means for large-scale implementation of antibody validation concepts proposed by an international working group on antibody validation (IWGAV).
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Neoplasm Proteins; nádory; Neoplasms; Humans; nádorové buňky kultivované; Proteomics; lidé; imunoprecipitace; proteomika; Immunoprecipitation; High-Throughput Screening Assays; Tumor Cells, Cultured; Antibodies; protilátky; rychlé screeningové testy; nádorové proteiny